Accuracy of dental implant placement with computer-guided surgery: a retrospective cohort study - Jeong-Kui Ku; Junggon Lee; Hyo-Jung Lee; Pil-Young Yun; Young-Kyun Kim (BMC, 2022)
Abstract Background The aim of this study was to assess the accuracy of virtual planning of computer-guided surgery based on the actual outcomes of clinical dental implant placement. Methods This retrospective study enrolled patients among whom implant treatment was planned using computer-guided surgery with cone beam computed tomography (CBCT). The patients who received implant according to the guide with the flapless and flapped approach were classified as group 1 and 2, respectively, and the others who could not be placed according to the guide were allocated to the drop-out group. The accuracy of implant placement was evaluated with the superimposition of CBCT. Results We analyzed differences in the deviated distance of the entrance point and deviated angulation of the insertion of implant fixtures. With regard to the surgical approach, group 2 exhibited greater accuracy compared to group 1 in deviation distance (2.22 ± 0.88 and 3.18 ± 0.89 mm, respectively, P < 0.001) and angulation (4.27 ± 2.30 and 6.82 ± 2.71°, respectively, P = 0.001). The limitations of guided surgery were discussed while considering the findings from the drop-out group. Conclusions Computer-guided surgery demonstrates greater accuracy in implant placement with the flapless approach. Further research should be conducted to enhance the availability of guides for cases with unfavorable residual bone conditions.